Reducing Cts Complaints and the Fatigue of Rock Breaker Through Ergonomics Approach By Exercising Nerve-Tendon Mobilization and Short Break - Utomo Wicaksono; I Made Muliarta; Luh Made Indah Sri Handari Adiputra (Eduvest - Journal of Universal Studies, 2021)
The ergonomics problem related to the casual laborers which here focus on rock breakers as their job, covers some aspects such as their muscle usage, working hours, postures, tools and environments. The ergonomics problem created health problems where the workers are having Carpal Tunnel Syndrome (CTS) and fatigue. This study intends to prove that exercising nerve-tendon mobilization and short break through ergonomics approach will be able to reduce the volume CTS complaints and the fatigue of the rock breakers. This study involves 7 samples from the controlling group and 7 samples from the intervention group. The CTS complaints are measured by using Symptom Severity Scale (SSS) from Boston Carpal Tunnel Questionnaire (BCTQ) and the fatigue was surveyed through 30 questionnaires from Item of Rating Scale of Industrial Fatigue Research Committee (IFRC). The Data were analyzed by applying Statistical Package for the Social Science (SPSS) software. The goals of this study is to give nerve-tendon mobilization exercise and short break through ergonomics approach related to the problem of muscle usage, working hours, postures, tools and environments would lessen the CTS complaints about 12,71% while the fatigue level in the amount of 5,69% that has been experienced by the rock breakers.